Genotype × environment interactions for grain iron and zinc content in rice. (19th May 2020) - Naik, Shilpa M; Raman, Anitha K; Nagamallika, Minnuru; Venkateshwarlu, Challa; Singh, Suresh Prasad; Kumar, Santosh; Singh, Shravan Kumar; Tomizuddin Ahmed,; Das, Sankar Prasad; Prasad, Krishna; Izhar, Tajwar; Mandal, Nimmai P; et al.
Abstract: BACKGROUND: Nutrient deficiency in humans, especially in children and lactating women, is a major concern. Increasing the micronutrient concentration in staple crops like rice is one way to overcome this. The micronutrient content in rice, especially the iron (Fe) and zinc (Zn) content, is highly variable. The identification of rice genotypes in which there are naturally high Fe and Zn concentrations across environments is an important target towards the production of biofortified rice. RESULTS: Phenotypic correlations between grain Fe and Zn content were positive and significant in all environments but a significant negative association was observed between grain yield and grain Fe and Zn. Promising breeding lines with higher Zn or Fe content, or both, were: IR 82475‐110‐2‐2‐1‐2 (Zn: 20.24–37.33 mg kg −1 ; Fe: 7.47–14.65 mg kg −1 ); IR 83294‐66‐2‐2‐3‐2 (Zn: 22–37–41.97 mg kg −1 ; Fe: 9.43–17.16); IR 83668‐35‐2‐2‐2 (Zn: 27.15–42.73 mg kg −1 ; Fe: 6.01–14.71); IR 68144‐2B‐2‐2‐3‐1‐166 (Zn: 23.53–40.30 mg kg −1 ; Fe: 10.53–17.80 mg kg −1 ) and RP Bio 5478‐185M7 (Zn: 22.60–40.07 mg kg −1 ; Fe: 7.64–14.73 mg kg −1 ). Among these, IR82475‐110‐2‐2‐1‐2 (Zn: 20.24–37.33 mg kg −1 ; Fe: 7.47–14.65 mg kg −1 ) is also high yielding with 3.75 t ha −1 . Kelhrie Cha (Zn: 17.76–36.45 mg kg −1 ; Fe: 7.17–14.77 mg kg −1 ), Dzuluorhe (Zn: 17.48–39.68 mg kg −1 ; Fe: 7.89–19.90 mg kg −1 ), Nedu (Zn: 18.97–43.55 mg kg −1 Fe: 8.01–19.51 mg kg −1 ), Kuhusoi‐Ri‐Sareku (Zn: 17.37–44.14 mg kg −1 ; Fe: 8.99–14.30 mg kg −1 ) and Mima (Zn: 17.10–45.64 mg kg −1 ; Fe: 9.97–17.40 mg kg −1 ) were traditional donor genotypes that possessed both high grain Fe and high Zn content. CONCLUSION: Significant genotype × location (G × L) effects were observed in all traits except Fe. Genetic variance was significant and was considerably larger than the variance of G × L for grain Zn and Fe content traits, except grain yield. The G × L × year variance component was significant in all cases. © 2020 Society of Chemical Industry